Elevated carbon dioxide increases soil nitrogen and phosphorus availability in a phosphorus‐limited Eucalyptus woodland. (9th February 2016) - Hasegawa, Shun; Macdonald, Catriona A.; Power, Sally A.
Abstract: Free‐air CO2 enrichment (FACE) experiments have demonstrated increased plant productivity in response to elevated (e)CO2, with the magnitude of responses related to soil nutrient status. Whilst understanding nutrient constraints on productivity responses to eCO2 is crucial for predicting carbon uptake and storage, very little is known about how eCO2 affects nutrient cycling in phosphorus (P)‐limited ecosystems. Our study investigates eCO2 effects on soil N and P dynamics at the EucFACE experiment in Western Sydney over an 18‐month period. Three ambient and three eCO2 (+150 ppm) FACE rings were installed in a P‐limited, mature Cumberland Plain Eucalyptus woodland. Levels of plant accessible nutrients, evaluated using ion exchange resins, were increased under eCO2, compared to ambient, for nitrate (+93%), ammonium (+12%) and phosphate (+54%). There was a strong seasonality to responses, particularly for phosphate, resulting in a relatively greater stimulation in available P, compared to N, under eCO2 in spring and summer. eCO2 was also associated with faster nutrient turnover rates in the first six months of the experiment, with higher N (+175%) and P (+211%) mineralization rates compared to ambient rings, although this difference did not persist. Seasonally dependant effects of eCO2 were seen for concentrations of dissolved organic carbon in soil solution (+31%), and there was also a reduction in bulk soil pH (‐0.18 units) observed under eCO2 . These results demonstrate that CO2 fertilization increases nutrient availability – particularly for phosphate – in P‐limited soils, likely via increased plant belowground investment in labile carbon and associated enhancement of microbial turnover of organic matter and mobilization of chemically bound P. Early evidence suggests that there is the potential for the observed increases in P availability to support increased ecosystem C‐accumulation under future predicted CO2 concentrations.